RESPIRE : breathing new life into bronchiectasis - Chalmers, James D. (2019)
RESPIRE, definable as “the recovery of hope, courage and strength after a time of difficulty”, is apt in the context of bronchiectasis therapy. Despite its recent renaissance, including the publication of the first international guidelines for the management of bronchiectasis, only a single treatment recommendation in the 2017 European Respiratory Society guidelines was supported by high-quality evidence [1]. This is a timely reminder of the real and challenging battle ahead, to deliver evidence-based appropriate and effective therapies to patients. In this issue of the European Respiratory Journal, a major “blow” in this battle has been struck and appears to have landed its intended target [2, 3]. The RESPIRE 1 and 2 trials evaluated 32.5 mg ciprofloxacin dry powder inhalation (DPI) administered twice daily versus placebo in two separate 2×2 arm trials. Taken together, these two trials represent the largest clinical trial programme ever conducted in bronchiectasis. Each trial studied a 14- and 28-day on/off drug regime over a 48-week period. The two trials differed by: 1) their enrolling countries; and 2) statistical handling of the data. RESPIRE 1 largely enrolled across Europe, North and South America, Australia and included Japan, while RESPIRE 2 focused on Asia and Eastern Europe. The inclusion criteria were the same for each set of trials, requiring patients with bronchiectasis infected with one of a list of the most commonly identified pathogens, and a history of ≥2 exacerbations in the previous year.